Is Teriparatide Beneficial to Spinal Fusion Surgery in the Older Patient?: A Narrative Review. Issue 5 (June 2019) - Wanderman, Nathan; Alvi, Mohammed; Yolcu, Yagiz; Carlson, Bayard; Sebastian, Arjun; Bydon, Mohamad; Freedman, Brett
Abstract : Since FDA approval in 2002, teriparatide has gained popularity as an anabolic therapy for the treatment of osteoporosis. Animal studies have suggested a role for teriparatide in spine surgery. Several recent studies have demonstrated adjunctive use of teriparatide in osteoporotic patients undergoing spine fusions improves fusion rates, decreases time to union, and decreases osteoporosis-related complications such as proximal junctional kyphosis. On the basis of the available literature, we outline an algorithm for the use of teriparatide in spine surgery.